PRINSIP RESPONSIBILITY TO PROTECT (R2P) DALAM KONFLIK ISRAEL- PALESTINA: BAGAIMANA SIKAP INDONESIA? - Setyo Widagdo; Rika Kurniaty (Arena Hukum, 2021)
AbstractThis article aims to discuss the Principles of Responsibility to Protect (R2P) that may be applied to the conflict in the Gaza Strip between Israel and Palestine. This normative legal research using a conceptual approach and a case approach indicates that the humanitarian crisis resulting from the conflict needs to be the focus of the international community, and the R2P principle may be applied as an alternative solution. Although the R2P principle is not a legal formulation, R2P plays an important role. It is recognized as an emerging norm or an obligation with a legal significance. R2P has been agreed upon and accepted by most countries globally that are members of the United Nations through UN General Assembly Resolutions. R2P assigns responsibility to the international community to help parties protect populations from the crime of genocide. Ultimately, R2P is expected to encourage states to fulfill their legal responsibilities and obligations, help build capacity to protect populations, and provide assistance to states in emergencies.Â AbstrakArtikel ini bertujuan untuk mendiskusikan Prinsip Responsibility to Protect (R2P) yang mungkin diterapkan pada konflik di jalur Gaza antara Israel dan Palestine. Penelitian hukum normatif dengan pendekatan konsep dan pendekatan kasus ini menunjukkan bahwa krisis kemanusian yang terjadi akibat konflik tersebut perlu menjadi fokus masyarakat internasional, dan prinsip R2P perlu untuk diterapkan sebagai salah satu alternatif solusi. Meskipun prinsip R2P bukanlah suatu rumusan hukum, R2P berperan penting dan diakui sebagai sebagai emerging norm, atau suatu obligation with legal significance. R2P telah disepakati dan diterima oleh mayoritas negara-negara di dunia yang menjadi anggota PBB melalui Resolusi Majelis Umum PBB. R2P memberikan tanggung jawab kepada komunitas internasional untuk membantu para pihak melindungi penduduk dari kejahatan genocide. Pada akhirnya, R2P diharapkan dapat mendorong negara untuk memenuhi tanggung jawab dan kewajiban hukum mereka, membantu membangun kapasitas untuk melindungi penduduk, dan memberikan bantuan kepada negara dalam keadaan darurat.